Insights into selected features of Pakistan’s most wanted terrorists - Saeed, Luqman (Terrorism and political violence, 2018)
This article attempts to provide insights into selected features of Pakistan’s most wanted terrorists using a dataset of 895 high-profile terrorists provided by the Counter Terrorism Wings of the Criminal Investigation Departments of regional police offices of Pakistan. It identifies spatial patterns of terrorist supply at subnational levels. The educational background of terrorists has also been analyzed. Noteworthy variations are observed in the supply of different types of terrorists across the geographical landscape of Pakistan. Findings also reveal that though terrorists are relatively more educated than the population group they emerge from, there is a higher probability of them emerging in districts with lower socio-economic performance.